2014
DOI: 10.1364/ol.40.000069
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state lasing in high-power InAs/GaAs quantum dots-in-a-well laser using active multimode interference structure

Abstract: We have designed and demonstrated InAs/GaAs quantum dots-in-a-well laser diodes for short cavities with transverse fundamental mode operation by using an active multimode interferometer (MMI) structure for the first time to the best of our knowledge. Room-temperature continuous-wave ground-state lasing at 1280 nm has been achieved with an output power of 116 mW per facet, which is 2.4 times higher than that of the conventional ridge laser diodes. By using the MMI structures, the excited-state (ES) lasing is ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…15,16 Therefore, the composite structural active zone of QDs and quantum wells is an effective candidate to capture more carriers for injecting into QDs. 17 Moreover, the quantum well in the QD/quantum well composite structural active zone can not only improve the carrier injection efficiency but also reduce the interfacial strain, which could decrease carrier and optical losses. 18,19 Liu et al prepared InAs QDs in InGaAs quantum well LDs, which demonstrated an ultra-low threshold current density that was even lower than that of quantum well LDs because the quantum well could help to capture and confine carrier motion to a two-dimensional plane.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Therefore, the composite structural active zone of QDs and quantum wells is an effective candidate to capture more carriers for injecting into QDs. 17 Moreover, the quantum well in the QD/quantum well composite structural active zone can not only improve the carrier injection efficiency but also reduce the interfacial strain, which could decrease carrier and optical losses. 18,19 Liu et al prepared InAs QDs in InGaAs quantum well LDs, which demonstrated an ultra-low threshold current density that was even lower than that of quantum well LDs because the quantum well could help to capture and confine carrier motion to a two-dimensional plane.…”
Section: Introductionmentioning
confidence: 99%
“…Early proposals with QDs [15] involved transitions between QDs in different layers, but the idea of using transitions inside a single QD was already suggested in Reference [16]. Later it was shown experimentally that QDs in general promise lower threshold currents than conventional laser diodes [17][18][19][20]. Recently, much experimental progress in the direction of QD intersublevel devices has been made with mid-infrared (mid-IR) photodetectors [21][22][23].…”
Section: Introductionmentioning
confidence: 99%